IMPACT OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES AT THE HEART OF DATA MANAGEMENT - Cédrick MOKILI MOKOSO, (IJRDO -Journal of Computer Science Engineering, 2025)
The impact of artificial intelligence (AI) technologies on data management is significant and rapidly evolving. AI enables the automation of large-scale data analysis, making it easier to identify patterns, trends, and anomalies. With machine learning algorithms, organizations can enhance real-time decision-making, optimize operational processes, and personalize customer experiences.Moreover, AI integration improves data security by detecting suspicious activities and preventing data breaches. It also aids in data classification and management, streamlining storage and access.However, the adoption of these technologies presents challenges, particularly regarding privacy and ethics. Concerns about algorithm transparency and bias management are critical, as decisions based on biased data can lead to unfair outcomes.In summary, while AI transforms data management practices, it necessitates careful consideration of ethical and regulatory issues.